2017
DOI: 10.1038/srep44898
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis miR396 mediates pathogen-associated molecular pattern-triggered immune responses against fungal pathogens

Abstract: MicroRNAs (miRNAs) play a pivotal role in regulating gene expression during plant development. Although a substantial fraction of plant miRNAs has proven responsive to pathogen infection, their role in disease resistance remains largely unknown, especially during fungal infections. In this study, we screened Arabidopsis thaliana lines in which miRNA activity has been reduced using artificial miRNA target mimics (MIM lines) for their response to fungal pathogens. Reduced activity of miR396 (MIM396 plants) was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 83 publications
(110 reference statements)
1
73
0
Order By: Relevance
“…Recently, it has been shown that MIM396 plants, with low miR396 activity, develop fast and strong immune responses and increased resistance to nectrotrophic and hemibiotrophic fungi, apparently by triggering defense priming 47 . Our results suggest that At-GRF3 could mediate similar responses as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that MIM396 plants, with low miR396 activity, develop fast and strong immune responses and increased resistance to nectrotrophic and hemibiotrophic fungi, apparently by triggering defense priming 47 . Our results suggest that At-GRF3 could mediate similar responses as well.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with many examples illustrating the costs of increasing defenses, where activation of immune pathways under non-stress conditions produces a fruitless diversion of energy that causes a negative effect on plant growth and fitness 48 . In turn, other plants with enhanced resistance and no fitness cost have also been described, including MIM396 itself 47 and overexpressors of NPR1 49 . Then, it is expected that rGRF3 plants may achieve a suitable balance to improve both stress response and growth under adverse conditions, however, we cannot exclude that GRF3 has different roles in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…conglutinans and Colletotrichum higginsianum. The MIM396 plant, in which miR396 activity is reduced, was more resistant to these fungal infections, whereas the overexpression of MIR396 increased plant susceptibility to fungal infections (Soto-Suárez et al, 2017). Moreover, slmiR482e-3p, which targets FRG3…”
mentioning
confidence: 99%
“…Each reaction was performed in triplicate with two biological replicates. ΔCT values were compared, as described by(Soto-Suárez et al, 2017). The sequence for all primers used in this work are found in…”
mentioning
confidence: 99%